エンドセリンETB受容体拮抗薬BQ788による頭部外傷マウスの炎症反応に対する抑制効果 - 小山, 豊; 菱沼, 滋; 小川, 泰弘; 道永, 昌太郎; 水口, 博之 (日本薬理学会年会要旨集, 2022)
Traumatic brain injury (TBI) is a fetal damage to the brain resulted from an external force to head by accidents and falls. One of the TBI-induced severe pathogenesis is an inflammatory damage. We previously suggested that BQ788, an endothelin ETB receptor antagonist alleviated blood-brain barrier disruption and brain edema in TBI mice. In this study, we investigated the effects of BQ788 on inflammatory reactions in TBI mice. As a model of TBI, a fluid percussion injury (FPI) was performed by a hydraulic impact on the mouse dura mater. BQ788 (15 nmol/day) was repeatedly administrated into lateral cerebroventricle from 2 to 5 days after FPI. As a maker of neutrophil, myeloperoxidase (MPO) and Ly6G were examined by fluorescent immunostaining. Expressions of inflammatory cytokines (tumor necrosis factor-α: TNF-α and interleukin-1β: IL-1β) and chemokines (monocyte chemoattractant protein−1: MCP−1 and mouse macrophage inflammatory protein-2: MIP-2) were measured by Real-time PCR. After FPI, MPO- and Ly6G-posotive cells were increased in the mouse cerebrum. Administration of BQ788 decreased these positive cells. Additionally, BQ788 decreased FPI-induced increases in expressions of TNF-α, IL-1β, MCP-1 and MIP-2 in the mouse cerebrum. These results suggest that ETB receptor antagonist alleviates TBI-induced inflammatory reactions.